2015
DOI: 10.3846/btp.2015.438
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Momentum Effect: a Case of Middle East Stock Markets

Abstract: Abstract. The objective of this paper is to find short term momentum effect in stock markets of the Middle East and to examine whether short term momentum profits can be explained by risk based CAPM model. Seven major stock markets from the Middle East were selected. Short term momentum effect was found in all seven stock markets and CAPM does not adequately explain the short term momentum profits but momentum portfolio returns are statistically significant. This paper is first attempt to bring major stock mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The momentum strategy yields on average 0.85 % per month across the countries. Ejaz and Polak (2015) tested the existence of the short-term momentum effect in 6 countries of the Middle East over the period 2008-2013 and found results confirming this anomaly. In India, Polak and Ejaz (2012) examined 4900 companies listed on Bombay Stock Exchange for the period going from June 2006 to June 2011 and found a short term momentum effect.…”
Section: Business and Economic Researchsupporting
confidence: 50%
“…The momentum strategy yields on average 0.85 % per month across the countries. Ejaz and Polak (2015) tested the existence of the short-term momentum effect in 6 countries of the Middle East over the period 2008-2013 and found results confirming this anomaly. In India, Polak and Ejaz (2012) examined 4900 companies listed on Bombay Stock Exchange for the period going from June 2006 to June 2011 and found a short term momentum effect.…”
Section: Business and Economic Researchsupporting
confidence: 50%
“…Besides these, other researchers have checked individually different stock markets over different time periods and have consistently reported positive abnormal returns after implementing momentum strategies. Some of these include Lui et al (1999) for the UK, Hurn and Pavlov (2003) for Australia, Mengoli (2004) for Italy, Cheng and Wu (2010) for Hong Kong, Pathirawasam and Kral (2011) for Sri Lanka and Ejaz and Polak (2015) for seven Middle East stock markets. However, apart from these studies, Chui et al and Wu (2011) reported low profitability of momentum strategies in Japanese and Chinese stock markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the significant and equally inconsistent behavioural, cultural and industry‐specific components explaining momentum return, only limited research has been carried out on the specific Islamic markets. For instance, Ejaz and Polak (2015) considered seven major Middle Eastern markets and found significant short‐term momentum returns in these markets. Narayan and Phan (in press) employed JT's framework to examine momentun returns in Islamic stocks, and found that momentun profit is significantly influenced by, among others, the value and size factors.…”
Section: Introductionmentioning
confidence: 99%